Aspects of the impact of the Sumerian language on the languages of other peoples - Youssef, Jassim Hussein (Journal of the College of Education for Girls for Humanities, 2023)
The Mamari line was written in the Sumerian language in the country of Elam (Iran) until the ancient Elam line appeared in the influence of the cuneiform line invented by the Sumerians in southern Mesopotamia. To the west of Iraq, the Italian mission in the city of Ibla (Tel Mardikh) A number of thousands of clay numbers are written in cuneiform script dating back to the dawn of the third dynasties, ie to the limits of 2450-2400 BC. These include economic and administrative texts as well as linguistic dictionaries. The Sumerian line also spread the Sumerian language from Assyria to Asia Minor at the beginning of the second millennium BC (in the 1950’s) by finding more than 3,000 cuneiform specimens in the Assyrian merchant colony uncovered by the excavations in the city of KolTeph (Kanch). Turkish territory ..The Sumerian cuneiform script has become the standard method of codification in a wide area of ​​the ancient Near East, especially in the Syrian and Palestinian territories, as evidenced by the cuneiform documents discovered in Mary (Tal Hariri), which highlighted the relations between the countries of the region in the era known as the Old Babylonian era Starting from 1800 BC. M . In later centuries, the cuneiform line was more widely used in the region than ever before by other non-Amorite peoples such as the Hittites in Anatolia, the Khorites, and the Mitnians in northern Syria. In 1400 BC, the Cuneiform Line became the means of codification of diplomatic documents between kings and princes And the rulers of Iraq, Syria, Palestine and Egypt as evidenced by the letters of Tel Amarna, and the Orratoru in Armenia, who used the cuneiform line in writing their language in the second half of the first millennium BC, the last people who borrowed the cuneiform line from Mesopotamia. The research included an explanation of the salient influences left by the Sumerian language in Egypt, Syria, Syria and Iran.